2007
DOI: 10.2528/pier07010501
|View full text |Cite
|
Sign up to set email alerts
|

Structural Parameters in the Formation of Omnidirectional High Reflectors

Abstract: Abstract-We investigate the structural parameters for the formation of omnidirectional photonic band gap in one dimensional photonic crystal. Simple transfer matrix method is used for calculations. The effect of two parameters, namely, refractive index contrast and filling fraction on omnidirectional reflection is investigated. We find from our study that when n L , n i , n s and d are fixed, omnidirectional bandgap increases with increasing n H /n L i.e., with increasing n H . Therefore, omnidirectional bandg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
0
15
1
Order By: Relevance
“…Using the unequal optical lengths in the constituent bilayer, PBG is also expected to be enhanced [14]. The PBG can be further significantly extended in a heterostructured PC that is formed by cascading two or more different PCs [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Using the unequal optical lengths in the constituent bilayer, PBG is also expected to be enhanced [14]. The PBG can be further significantly extended in a heterostructured PC that is formed by cascading two or more different PCs [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…PCs have drawn much attention as a new kind of optical materials [12,13]. These materials have many potential applications in optoelectronics and optical communication [13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Also, 1-D photonic crystal made of Si was theoretically studied for high frequency range of omnidirectional reflection by Singh et al Singh et al, 2007) and Thapa et al (2006) who investigated 1-D omnidirectional high reflector for infrared wavelengths. They demonstrated that, two Si-based photonic crystals increase the frequency range of OBG by overlapping.…”
Section: Introductionmentioning
confidence: 99%